Social Inequalities in Argentina and Chile: A Comparative Analysis of Welfare Models, Labour Policies, and Occupational Trajectories from a Biographical Perspective - Muñiz Terra, Leticia Magali (2022)
The article analyses the configurations of social inequality in Argentina and Chile between 2000 and 2019 through a comparative biographical approach that combines three dimensions: macro-social (welfare models), meso-social (labour policies), and micro-social (occupational trajectories). In Argentina, welfare schemes oscillated between moderate protectionism and a liberal approach; in Chile, a movement was observed between revised neoliberalism and a protectionist liberal welfare approach. Regarding labour policies, a transition from employment regulation to self-management was observed in the Argentine job market; in Chile, a meritocratic discourse remains that advocates for worker self-management, regardless of changes in welfare schemes. These differences have no appreciable impact on the configuration of class trajectories, which are similar in both countries. While the service classes generally construct advantageous trajectories, the intermediate classes are ambivalently affected by crises and insufficient protection and the working classes accumulate disadvantages since they are conditioned by welfare schemes and social-labour policies.